Development of an urban concept hybrid vehicle - Denoga, Gerald Jo C.; Balbarona, Juvy A.; Eusebio, Tito N. Jr.
The research is about the development of a diesel hybrid vehicle. A small concept car was prototyped aimed at achieving high fuel mileage while still satisfying other consumer needs like speed, aesthetics, safety, usability and comfort. The design is comprehensive, including lightweight chassis design, aerodynamic shell design, calculated passenger safety and optimized power generation. Aerodynamic design was done to provide input to the power requirements. The drive train is based on a series hybrid system, using a single cylinder diesel engine, an electric DC generator, a motor and a super capacitor. The key feature of the drive train is the control system that ensures a fixed power draw from the engine corresponding to the load and speed of the diesel engine at optimum brake specific fuel consumption.
Keywords: Diesel hybrid..; Aerodynamic design; Engine map; Series hybrid